2014
DOI: 10.1021/jf5038689
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Chemical Characterization, and Free Radical Scavenging Activity of Phenolics from Triticum aestivum L. Aerial Parts

Abstract: Fourteen phenolic compounds (flavonoids and phenolic acids) were isolated and 19 were identified in the aerial parts of Triticum aestivum L. The structures of these compounds were established on the basis of the data obtained by electrospray ionization-mass spectrometry (ESI-MS) and nuclear magnetic resonance (NMR) techniques. T. aestivum L. was found to be rich in flavones, especially in luteolin derivatives. Three of the isolated compounds, including luteolin 6-C-[6Glc″-O-E-caffeoyl-β-D-glucopyranosyl(1″→2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The identification results of the compounds are listed in Table 1. Peaks 1 and 2 show the molecular ions of m/z 579 [M-H]and m/z 563 [M-H] -, respectively, and have retention times higher than that of peak 3 (isoschaftoside), and were reported previously as luteolin 6-C-pentoside 8-C-hexoside and apigenin 6-C-hexoside 8-C-pentoside [25][26][27], respectively; thus, in this study, peaks 1 and 2 were identified as luteolin 6-C-hexoside 8-C-pentoside and apigenin 6-C-hexoside 8-C-pentoside, respectively. Peak 4, appearing between the retention times of peaks 3 (isoschaftoside) and 5 (isoorientin), with a molecular ion of m/z 593 [M-H] -, was identified as apigenin-6,8-di-C-hexoside [27].…”
Section: Identification Of the Compoundsmentioning
confidence: 85%
See 4 more Smart Citations
“…The identification results of the compounds are listed in Table 1. Peaks 1 and 2 show the molecular ions of m/z 579 [M-H]and m/z 563 [M-H] -, respectively, and have retention times higher than that of peak 3 (isoschaftoside), and were reported previously as luteolin 6-C-pentoside 8-C-hexoside and apigenin 6-C-hexoside 8-C-pentoside [25][26][27], respectively; thus, in this study, peaks 1 and 2 were identified as luteolin 6-C-hexoside 8-C-pentoside and apigenin 6-C-hexoside 8-C-pentoside, respectively. Peak 4, appearing between the retention times of peaks 3 (isoschaftoside) and 5 (isoorientin), with a molecular ion of m/z 593 [M-H] -, was identified as apigenin-6,8-di-C-hexoside [27].…”
Section: Identification Of the Compoundsmentioning
confidence: 85%
“…The flavonoids in the 37 wheat sprout samples, including the original cultivar (PL01), certified cultivar ("Geumgang"; PL26), and mutant lines (PL05, PL06, PL08-PL11, PL13-PL20, PL23-PL25, PL41, PL42, PL44, PL46-PL48, and PL50-PL61), were analyzed using HPLC-DAD-ESIMS. Then, 14 peaks in their chromatograms were speculated and identified by comparing their retention time, ultraviolet (UV) spectra, and negative molecular ions with those of the compounds purchased in this study or with those reported previously [24][25][26][27][28]. Peaks 3, 5, and 11 were assigned to isoschaftoside, isoorientin, and isoscoparin, respectively, which were unambiguously identified by comparing the retention times and molecular weights with those of the reference standards.…”
Section: Identification Of the Compoundsmentioning
confidence: 85%
See 3 more Smart Citations